PHILOSOPHICAL REFLECTIONS IN SUFI THOUGHT - Tursunkulova Shakhnoza Tuychievna (Web of Journals Publishing, 2025)
This article analyzes the main ideas of Sufi philosophy, particularly the essence of existence and non-existence, the inner meanings of the concepts of nafs, heart, and soul, as well as the interpretation of the process of spiritual purification in Sufi sources. Through the symbols frequently found in the works of Jalal al-Din Rumi such as the mirror, light, nothingness, and perfection the human spiritual world, self-realization, and inner elevation are explained.
Keywords: Sufism, spiritual purification, philosophy of existence, nafs, heart, soul, perfect human, mirror symbolism, inner beauty, spiritual elevation.